ABSURDITY: INTERPRETING ON THEATRE THROUGH EXISTENTIALISM APPROACH - Marleen M.A.F.Q. Sumampouw; Yuri Lolita; Orestis Soidi (UICELL, 2021)
The aims of the study to find an ideal approach to enhance students in this theatre course and facilitate them for literature understanding through several literature theories. This study proposed a sociological literature approach with two elements. There are consist of the sociology of the author and the sociology of literature. To explain Existence on the absurdity of the character, Existence on the collective absurdity, Existence of personality structure based on data. The existentialism approach was also used to solve the complexity of concepts in each drama script. Through the two elements of the sociology of literature, we acquired that the essence of existentialism is the term exists, as Camus’s work on rebellion theme, I rebel; such as, I exist. Talking about the absurdity of literary works is talking about the notion of absurdity itself and the notion of its feeling, and then about attitudes determining our actions. Absurdity also needs to be explored through emotions and intertextuality. Keywords: absurdity, existentialism, drama. theater